BIOMASS REDUCTION OF ORGANIC MATERIALS IN A DOMESTIC COMPOSTING SYSTEM - Vasconcelos, Osmar Luis Silva; Carneiro, Laiza Moraes; Marques, Georgiana Eurides de Carvalho; Nojosa, Ellen Cristine Nogueira; Lorena, Rodrigo Barbosa (Biofix Scientific Journal, 2021)
The population growth of urban cities has led to an increase in the demand for food and, consequently, in greater quantities of solid organic waste destined for landfills and/or dumps. The objective of this work was to evaluate the effect of temperature on household organic waste in reducing biomass through the domestic composting process. The waste was collected with 5 families (F1, F2, F3, F4 and F5) located in a neighborhood of São Luis and deposited in compost containers made with plastic containers with a capacity of up to 15 kg of waste. A period of 95 days was adopted to finalize the process. The temperature parameter was performed with the aid of a chemical thermometer and the biomass loss was calculated taking into account the initial weight minus the final weight divided by the initial weight of the biomass, a result given in percentage. The temperatures reached by all composters were, on average, above 40° C in the thermophilic phase and 30° C in the mesophilic phase, the biomass reduction was over 50% in all composters, with emphasis on F1, which reached a percentage above 70%. Other factors such as the presence of ants spp., larvae of Hermetia illucens (L., 1758) (Diptera: Stratiomyidae), aeration and types of residues may also have affected the percentage of biomass loss. These data are important because they will serve as a planning basis for future work, with the possibility of using larger areas destined for composting and, consequently, higher volumes of organic solid waste will no longer be sent to landfills, dumps or in inappropriate places.